Micturition. Issue 7 (July 2021) - Elsayed, Eslam; Davies, Susie
Abstract: The lower urinary tract function is to store and void urine (micturition) that has been produced by the kidneys and transferred to the bladder via the ureters. The lower urinary tract consists of the bladder, urethra and (in males) the prostate. A complex interaction of central, autonomic and somatic innervation enables micturition to be under voluntary control. Common disorders of micturition include bladder outflow obstruction and overactive bladder syndrome, and management of these disorders may include conservative, pharmacological or surgical interventions.